A method to prepare reference colors for chromatic adaptation experiments. Issue 4 (17th January 2022) - Cai, Shengyan; Sun, Yan; Sun, Ruixia; Chen, Xiaoying; Shi, Xinyue
Abstract: The preparation of the reference colors is the hardest and the most time‐consuming part of chromatic adaptation experiments. In this paper, a new method is proposed to prepare high‐quality reference color arrays for chromatic adaptation experiments. The reference color arrays are defined in the a*b* plane of CIELAB color space. The initial arrays are calculated by the CAT02 and the desired color differences. Then the arrays are output and two visual experiments are organized, the chromatic adaptation experiment and the color difference estimating experiment. The former is to check if the color gamut of the reference colors is fit for the experiment. The latter is to check the uniformity of the color differences of the arrays. According to the fitting curves from the color differences estimating experiment, the reference color arrays can be optimized to be more uniform in the color differences. The method is proved effective and suitable for different media. Abstract :